“Are we one member in a family of nations, or a country that prefers to keep itself to itself and bolt the door?” : Constructed oppositions creating representations in UK Online Newspaper Editorials’ Brexit discourse - Kortelainen, Katariina (My University, 2021)
This thesis examines the construction of opposites using syntactic frames (such as X, not Y) and how these oppositions are used to convey different representations. The material of this study comes from (online) newspaper editorials of four British newspapers on the topic of Brexit, The Guardian, The Telegraph, The Mirror and the Daily Mail. The main aspect of the study is to examine the differences in representations in these newspapers. Additionally, this thesis also examines the kinds of syntactic and conceptual triggers that create oppositions in the Brexit editorials. The methods used in this thesis are mainly based on Matt Davies’ (2008 and 2012) research on syntactically triggered oppositions, especially his typology of oppositions, outlining eight categories of oppositions based on the syntactic frames that trigger them. After the initial categorisation and analysis of oppositions, selected examples of two emerging themes, representations of Britain, and representations of “the elite” and “ordinary people” were analysed qualitatively. The results of this study indicate that desirable Britain was represented as connected, active, powerful, global and open across all the newspapers regardless of their different stances on Brexit. However, the pro-Remain papers also represented desirable Britain as united and inclusive, whereas pro-Leave papers saw desirable Britain as independent and free. Elites and ordinary people were generally opposed against each other. Elites were represented as rich, arrogant and selfish, and ordinary people as poor, humble and selfless. There was a slight difference between the broadsheet and tabloid newspapers’ representations in this theme, which could be because of their different target audiences. The data contained examples of oppositions from all of Davies’ categories. However, some syntactic triggers that did not belong to any of the categories were also found to create oppositions. This offers a topic for further research. Constructed oppositions have not been studied very excessively, so this thesis aims to answer to that, but further research on the topic is still needed.
Keywords: opposition, antonymy, syntactic triggers, ideology, UK, editorials, Brexit, discourse